Contratos empresariais de colaboração: a resilição unilateral e a proteção dos investimentos - Duarte, Victória Albertão (2020)
The current research analyzes the protection of investments that were made for the execution of commercial contracts in the event of unilateral termination, especially based on cases judged by Brazilian Superior Court of Justice. Article 473, sole paragraph of the Civil Code ensures suspension of the effectiveness of the complaint in cases where substantial investments have been made, if they have not yet been recovered at the time of the termination. However, there are certain cases where compulsory extension of contracts may not represent an efficient alternative for the parties, especially in collaborative contracts. Besides collaborative contracts, in other legal categories, the nature of the contract may be incompatible with compulsory extension, especially considering contracts where trust is an essential element and that there is a need for cooperation between the parties to achieve the objectives of the contractual relationship.